2015
DOI: 10.1177/0967772015619303
|View full text |Cite
|
Sign up to set email alerts
|

The doctor as an artist

Abstract: Charles Bell, Francis Seymour Haden, Jean-Martin Charcot, Paul Richer, Henry Tonks and Harry Lamb were gifted draughtsmen. Some used their skills to illustrate their work, a few abandoned medicine altogether to become artists in their own right. With the exception of Haden few were able to combine an artistic and a medical career. Their medical training and their wartime experiences influenced their artistic portrayal of the wounded. Their significant contribution, however, resides in the way in which they inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The young Jean-Martin had already shown specific artistic abilities. His father had suggested that his son should become an artistic painter [7, 8, 12, 13].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The young Jean-Martin had already shown specific artistic abilities. His father had suggested that his son should become an artistic painter [7, 8, 12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Like Charcot, a number of neuroscientists were also skilled artists and draftsmen: these include Charles Bell (1774-1842), Pierre Samuel Toussaint Fromentin-Dupeux (1786-1867), Frédéric Estre (1813-1902), Paul Richer (1849-1933), and the brothers Santiago (1852-1934) and Pedro Ramón y Cajal (1854-1950) [11][12][13][14]. The Cajals and Bell used these skills to illustrate their work [11][12][13][14]. Bell combined his varied artistic and scientific talents in detailed anatomical and surgical illustrations and paintings in several books.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it should be noted that also working place is in the conflict area, some physicians can still have a good job and present good humanistic piece of work. The world famous physician and artist, Henry Tonks, is the good example [5][6][7].…”
mentioning
confidence: 99%